Powerlifting practices in compensatory fatigue phase to improve shooting accuracy in basketball - Rogozhnikov, M. A.; Dementiev, K. N.; Volsky, V. V.; Sergeeva, A. G. (Theory and Practice of Physical Culture, 2019)
Shooting accuracy in basketball is known to be best trained in the compensatory fatigue phase with the progressively growing general fatigue when the athlete is still able to cope with the game intensity for some time by the individual adjustments to the movement biomechanics.